EKSTRAKSI DAUN PEPAYA, DAUN MENGKUDU DAN SERAI WANGI (STUDI EKSPLORATIF ETNOBOTANI PESTISIDA ALAMIPADA TANAMAN BAYAM) - Hernimae Wau; Yan Piter B. Ziraluo; Murnihati Sarumaha (Tunas: Jurnal Pendidikan Biologi, 2020)
The study aims to find out the benefits of the ekstraction of papaya leaves, potted leaves and spikenard as natural pesticides to the spinach plant. In this study a sort of qualitative work with a descriptive approach. The research population is a spinach plant of 20 polypods still in treatment. The sample of this study was selected to get the pests to be in basic. The results of this study are in the knowing that the benefits of papaya leaf extraction, leaning and seagan as a natural pesticide in spinach plants, whit spraying mixed papaya leaf extracts, leaning civilian and paragged as spray spinning plant by pest. The benefits of this research are guidelines and sources of information in carrying out research or agricultural activities to find out the benefits and use of extraction of papaya leaves, shafted and spikenard as natural pesticides to the spinach plant. As well as knowledge of societies in order to use and exploit extracts of papaya leaves, pigmentation and spikenard as natural pesticides to the spinach plant and utilize existing natural resources and reduce the use of synthetic pesticide.